2015
DOI: 10.7554/elife.05055
|View full text |Cite
|
Sign up to set email alerts
|

The contrasting phylodynamics of human influenza B viruses

Abstract: A complex interplay of viral, host, and ecological factors shapes the spatio-temporal incidence and evolution of human influenza viruses. Although considerable attention has been paid to influenza A viruses, a lack of equivalent data means that an integrated evolutionary and epidemiological framework has until now not been available for influenza B viruses, despite their significant disease burden. Through the analysis of over 900 full genomes from an epidemiological collection of more than 26,000 strains from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
222
3
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(268 citation statements)
references
References 62 publications
31
222
3
12
Order By: Relevance
“…Nevertheless, both lineages cocirculated each year. Data from other countries and from another Australian study found that B/Victoria cases were younger than cases with B/Yamagata infection 33, 54, 55. Our results showed the only age group with a trend towards a higher proportion of Victoria lineage was 10‐ to 19‐year‐olds.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Nevertheless, both lineages cocirculated each year. Data from other countries and from another Australian study found that B/Victoria cases were younger than cases with B/Yamagata infection 33, 54, 55. Our results showed the only age group with a trend towards a higher proportion of Victoria lineage was 10‐ to 19‐year‐olds.…”
Section: Discussionsupporting
confidence: 48%
“…Mismatch between the TIV's influenza B lineage and the circulating B lineage occurs at approximately two‐ to four‐year intervals in many countries 18. In Australia, partial or complete mismatches of B with circulating lineage have been reported 33. It is not fully understood whether vaccination with one B lineage confers significant protection against the other.…”
Section: Introductionmentioning
confidence: 99%
“…Influenza A viruses attract the greatest attention due to infrequent infections of humans with zoonotic viruses, the potential to give rise to pandemic viruses through genetic reassortment and antigenic shift, sustained antigenic drift, extensive spread, and varied severities of disease (1). In contrast, influenza B viruses are confined largely to humans, antigenic drift of these viruses occurs at a lower rate, and these viruses do not undergo antigenic shift (1,2). The severity of disease caused by influenza virus is considered unpredictable (3), yet, until recently, infections with influenza B viruses were considered to be mild compared to infections with influenza A viruses (4) and to account for a reduced burden of disease.…”
mentioning
confidence: 99%
“…The Victoria lineage is subject to stronger seasonal bottlenecks, higher transmission rates, greater antigenic variation, and stronger positive selection and infects mostly younger age groups. In contrast, the Yamagata lineage experiences less severe bottlenecks and infects older people (3). In tropical Kuala Lumpur in Malaysia, there is year-round influenza activity, with biannual epidemics in May to July and November to January (4).…”
mentioning
confidence: 99%